Hurricanes and typhoons - Dineen, Jacqueline (New York : Gloucester Press, 1991)
An introduction to violent storms, discussing weather patterns, damaging effects, human causes, monitoring equipment, and what can be done to protect people and property.
Includes index.
7.3
7.3
5-8.
5-8
Keywords: Hurricanes -- Juvenile literature; Storms -- Juvenile literature; Typhoons -- Juvenile literature; Hurricanes; Storms; Typhoons; Hurricanes; Storms; Typhoons